The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/pc.24214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of process parameters on fracture toughness of PP/EPDM/nanoclay nanocomposite fabricated by novel method of heat assisted Friction stir processing

Abstract: Thermoplastic elastomeric nanocomposites due to their excellent mechanical, thermal, and chemical properties have a wide application in airplane, shipbuilding, and automotive industries and medical apparatus. Friction stir processing (FSP) is a novel technique for the fabrication of composites, nanocomposites and microstructural modifications. In this paper, polypropylene/ethylene-propylene-diene monomer (PP/EPDM) nanocomposite with 5 wt% nanoclay are fabricated by FSP to determine the effect of process parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…There are some works that have investigated the effects of these parameters on the dispersion state of the fillers in the polymer matrix. [28,29] Sui et al [28] investigated the filler dispersion state of MWCNT-TPU composite in different processing conditions via melt mixing and solution mixing methods. They showed that the solution method leads to a better dispersion at relatively low content of the filler (<2.5 wt%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some works that have investigated the effects of these parameters on the dispersion state of the fillers in the polymer matrix. [28,29] Sui et al [28] investigated the filler dispersion state of MWCNT-TPU composite in different processing conditions via melt mixing and solution mixing methods. They showed that the solution method leads to a better dispersion at relatively low content of the filler (<2.5 wt%).…”
Section: Introductionmentioning
confidence: 99%
“…There are some works that have investigated the effects of these parameters on the dispersion state of the fillers in the polymer matrix. [ 28,29 ]…”
Section: Introductionmentioning
confidence: 99%
“…The fracture toughness of tough polymer nanocomposite was studied with essential work of fracture method . Khodabandelou et al and Mostafapour et al conducted experiments on PP/EPDM blend with carbon nanotube and nanoclay particles, respectively. They concluded that main fracture mechanism in un‐vulcanized samples was the formation of dilatation and compatibilized blends increased the fracture toughness significantly.…”
Section: Introductionmentioning
confidence: 99%
“…They found that both CB and CNT increased mechanical properties of PP/EPDM, while dispersion was the main factor rather than weight fraction. Khodabandelou et al, [36] and Mostafapour et al, [23] used CNT and NC, respectively, to investigate fracture mechanisms of PP/EPDM/nanofiller nanocomposites. The main fracture mechanism in the unvulcanized samples proved to be formation of dilatation.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Ethylene propylene diene monomer (EPDM) is one of the most effective tougheners for PP. [17][18][19][20][21][22][23] Toughness of PP/EPDM can be increased more by vulcanization process. [24,25] Despite unique properties provided by EPDM rubber phase, it reduces PP stiffness.…”
Section: Introductionmentioning
confidence: 99%